The Debate on the Concept of the Person in Bioethics - Hołub, Grzegorz (Studia Ecologiae et Bioethicae, 2020)
This article endeavours to sketch the debate about the concept of a person in the realm of bioethics. Initially, it sets out three understandings of the issue, namely the concept of a person in naturalistic philosophy, in the current of communitarianism and in one of the humanistic positions. The analysis of these approaches lead to the conclusion that a human person is perceived either as an empirical and psychological entity or as a free subjectivity creating him/herself. This thesis provides stimulation for further research. In order to avoid a kind of dualism in the perception of a person stemming from the stances outlined above, the personalistic approach is developed. This points out that a human being should be depicted as one indivisible entity unifying in itself more strictly its self, a subjective aspect of the person, with nature-body aspect which is an objective facet of being human. Given this personalistic perspective, a person comes out as an embodied subjectivity formed by the unique personal act of existence. In this article, such a concept of a person is argued as a vital support in the complex field of bioethical dilemmas.